Analysis Effectiveness and Efficiency Management Budget Village Regional Income and Expenditures in Sanur Kaja Village, Regency Badung, Bali - Nurul Qalbi Insaniah; Ansar Setiawan N; Nur Hafsa; Sri Putri Wahyuni; Hapriansyah Harun S; Izzati Saputri. A; Muttiarni (Pustaka Digital Indonesia, 2024)
Sanur Kaja Village is a village located in South Denpasar District, Denpasar City, Bali. As part of a famous tourism area, Sanur Kaja has significant economic potential from the tourism and cultural sectors. However, the management of the Village Revenue and Expenditure Budget (APBD) in Sanur Kaja is the main focus in efforts to improve the welfare of local communities and develop basic infrastructure. This research applies analytical verification methods with a quantitative approach. Researcher use secondary data sources like articles , news from online media, journals , books , documentation and sources other. Collected data will processed For produce information that provides description about condition object research and information related Budget Regional Income and Expenditures (APBD). The results of the analysis have been done researcher 3 years final from 2021 to 2023 shows​ that level the average effectiveness reaches 82% and level efficiency reached 85%. This indicated that management finances in the village Sanur kaja done with Enough Good . . Writer hope APBD management in villages Sanur kaja Can more optimal with method Need done evaluation deep to fluctuation income original area For identify the cause and take steps For increase its stability . Government area can consider diversification source income or increase efficiency in management existing income